Complement cascade on severe traumatic brain injury patients at the chronic unconscious stage: implication for pathogenesis. (3rd August 2018) - Bao, Wangxiao; He, Fangping; Yu, Lihua; Gao, Jian; Meng, Fanxia; Ding, Yahui; Zou, Hai; Luo, Benyan
ABSTRACT: Background : Patients who awake from severely traumatic brain injury (TBI) may remain unconscious for many years. Although behavioral assessment and functional imaging are currently used as diagnostic tools, the molecular basis underlying chronic condition has yet to be explored. Method : Plasma samples were obtained at 3 time points (1, 3 and 6 months) from 18 patients with chronic disorders of consciousness who survived severe TBI, and 6 healthy volunteers. A coupled isobaric tag for relative and absolute quantitation (iTRAQ)-based proteomics approach was used to screen differentially expressed proteins (DEPs) between patients and controls. Potential molecular mechanisms were further discussed through bioinformatics analyses. Result : In total, 300 plasma proteins <1% false discovery rates were identified and 32 proteins were consistently altered between patients and controls. Biological pathway analysis revealed that the DEPs were predominantly involved in complement cascade. Conclusions : This study discussed potential mechanisms of complement cascade underlying chronic stage in severe TBI.